Expressão da p27 no carcinoma mamário em pacientes na pós-menopausa expostas á hormonioterapia, e sua correlação com outros biomarcadores - Portela, Rachel Machado de Oliveira [UNIFESP] (2014)
Background: Mutations in genes that regulate cell cycle are found in most human cancers. p27 is a member of the Cip/Kip family of cyclin-dependent kinase inhibitors and it is present in high levels in quiescent cells, but its levels decline when cells proliferate in response to mitogenic signals. Various functions have been attributed to p27, including promotion of apoptosis and regulation of drug resistance. There is evidence from preclinical studies that p27 is essential for cell cycle arrest by Tamoxifen and other antiestrogenic drugs. Objectives: To describe and compare the expression of nuclear and cytoplasmic p27 in hormone sensitive invasive breast carcinomas in postmenopausal women, prior and after tamoxifen and anastrozole in a short-term treatment, and to compare the expression of nuclear p27 with clinical and pathological data and biomarkers. Methods: Fifty-eight patients with hormone receptor positive invasive breast carcinomas (stage II or III) were double blind randomized in a prospective placebo controlled study with short-term hormone treatment (HT) groups for 21-28 days prior surgical treatment: Anastrozole, Placebo and Tamoxifen. Pre and post HT samples were disposed in tissue microarray blocks and submitted to immunohistochemical evaluation using semi-quantitative Allred?s method for nuclear biomarkers, and Herceptest score for HER-2 and cytoplasmic p27. Statistical analysis were performed using the GEE (General Estimulation Equations) and ANOVA tests with significant p?0.05. Results: There was no statistically significant correlation between nuclear p27 expression and tumor size neither histologic grade. After short-term HT there was an increment of cytoplasmic p27 on all groups, and the same was observed with nuclear p27 after Anastrozole and Placebo. There was a positive correlation between Ki-67, cyclin D1, p53 and nuclear p27 prior to HT. After HT there was a positive correlation between Ki-67, cyclin D1, HER-2, ER (estrogen receptor) and nuclear p27. Conclusion: p27 predictive value was not clear. The positive correlation between nuclear p27 and poor prognostic makers was unexpected.